Impact of sacubitril/valsartan on heart failure admissions: insights from real-world patient prescriptions. Issue 2 (4th March 2019) - Martens, Pieter; Lambeets, Seppe; Lau, Chirik Wah; Dupont, Matthias; Mullens, Wilfried
Abstract: Background: Sacubitril/valsartan reduced heart failure (HF)-admissions and cardiovascular mortality in the PARADIGM-HF-trial. However, real-world patients are often frailer and less able to tolerate high doses of sacubitril/valsartan. Methods: We performed a retrospective analysis of consecutive patients prescribed sacubitril/valsartan in a single tertiary HF-clinic between December 2016 and January 2018. HF-admissions were assessed in a paired fashion, comparing the amount of antecedent HF-episodes with incident HF-episodes after the initiation. Baseline risk for adverse events was assessed by the EMPHASIS-HF-risk-score. Results: A total of 201-HF-patients were retrospectively identified (age = 68 ± 11 years, ejection fraction = 29 ± 8%). Real world patients were older, had higher serum creatinine and a higher New-York Heart-Association (NYHA)-class ( p  < .05 for all) than in the PARADIGM-HF trial. Over a mean duration of 221 ± 114 days after initiation of sacubitril/valsartan a total of 23-individual patients experienced at least one HF-episodes. Over the same time period preceding initiation of sacubitril/valsartan, 51 individual patients experienced a HF-episodes ( p  < .001). Sacubitril/valsartan significantly reduced the rate of incident vs. antecedent HF-admissions, in patients with low or high baseline NYHA-class (II vs. III and IV; p value = 0.019 respectively p  = .004) or patients with an EMPHASIS-HF risk score below or above the mean ( p  = .002 respectively p  = .016). Patients older than 75-years exhibited a trend towards HF-reduction. Higher doses of sacubitril/valsartan were associated with more reduction in incident versus antecedent HF-episodes. Conclusion: Despite being frailer and older, real-world patients exhibit a significant and early reduction in incident HF-hospitalisations following initiation of sacubitril/valsartan. Higher doses might be associated with more reduction in HF-admissions, underscoring the importance of dose uptitration.